Rapid recovery from acoustic trauma: chicken soup, potato knish, or drug interaction? - Cacace, Anthony T.; Silver, Steven M.; Farber, Martha (American journal of otolaryngology, 2003)
Objectives: To describe the phenomenology and consider possible mechanisms mediating rapid and unexpected recovery from acoustic trauma after ingestion of a food substance (potato knish). Study Design: Single subject with repeated test measures. Setting: Regional Veteran’s Administration Medical Center, tertiary care medical center. Methods: Pure-tone audiometry and distortion product otoacoustic emissions (DPOAEs) performed at 6 days, 21 days, and 1 year postexposure. Results: Medical treatment with corticosteriods and a diuretic alone failed to improve auditory function and related symptoms (tinnitus and aural fullness) over a 2-week period. Rapid recovery of auditory function (dramatic improvement in pure tone thresholds; reappearance of DPOAEs) and abatement of related symptoms directly followed physiologic reactions from ingesting a food substance. Conclusions: Rapid recovery from acoustic trauma was temporally correlated with urodynamic and cardiovascular reactions from ingesting food containing sulfite preservative, a substance to which the individual was allergic. Factors that may have contributed to recovery of function include massive diuresis, increased heart rate, release of biochemical mediators, mediator-induced vasodilatation, and changes in vascular or cell membrane permeability. Establishing relationships that lead to recovery of function from acoustic trauma may facilitate research and aid in the development of new treatment options for this condition.